2019
DOI: 10.1002/jcb.29188
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells regulate TGF‐β to adjust neuroinflammation in postoperative central inflammatory mice

Abstract: Background Postoperative cognitive dysfunction (POCD) is one of the common postoperative complications, which is more common in aged patients. POCD mainly manifests as cognitive function changes after surgery, such as memory decline and inattention. In some severe cases, patients may suffer from personality changes and (or) social behavior decline. The aim of the current study is to confirm the effect and elucidate the mechanism of bone marrow mesenchymal stem cells (BMSCs) in postoperative central inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Massive evidence showed that major surgeries could induce a widespread systemic inflammatory response, and multiple biomarkers of neuro-inflammatory response were widely observed to have an association to the pathophysiological changes underpinning POCD and cognitive deficits in clinical studies [ 4 , 5 ]. This conclusion was verified in multiple surgery rodent models in terms of its mechanism, showing that the upregulation of pro-inflammatory cytokines and inflammatory mediators in the central nervous system (CNS) could cause obvious cognitive impairment in animals, and that it could be blocked by anti-inflammatory agents [ 6 , 7 , 8 ]. Inflammation leads to oxidative stress, contributes to mitochondrial dysfunction [ 9 , 10 , 11 , 12 ], and induces a variety of metabolic disorders, such as iron metabolism disorders.…”
Section: Introductionmentioning
confidence: 94%
“…Massive evidence showed that major surgeries could induce a widespread systemic inflammatory response, and multiple biomarkers of neuro-inflammatory response were widely observed to have an association to the pathophysiological changes underpinning POCD and cognitive deficits in clinical studies [ 4 , 5 ]. This conclusion was verified in multiple surgery rodent models in terms of its mechanism, showing that the upregulation of pro-inflammatory cytokines and inflammatory mediators in the central nervous system (CNS) could cause obvious cognitive impairment in animals, and that it could be blocked by anti-inflammatory agents [ 6 , 7 , 8 ]. Inflammation leads to oxidative stress, contributes to mitochondrial dysfunction [ 9 , 10 , 11 , 12 ], and induces a variety of metabolic disorders, such as iron metabolism disorders.…”
Section: Introductionmentioning
confidence: 94%